Implementation of problem-based learning assisted by geometry-based student worksheets to improve mathematics learning outcomes of 8th grade students - Anindya Hawa Ainul Fanfa; Muhamad Toyib (Universitas Islam Negeri Raden Intan Lampung, 2025)
This finding is motivated by the importance of improving mathematics learning outcomes through the application of effective learning methods. The purpose of the finding is to determine the effect of Problem Based Learning (PBL)-based learning with the utilization of Magnetic Ball-based Student Worksheets (MBSW) on the mathematics learning outcomes of eighth-grade students at MTsN 1 Wonogiri. This experimental research uses a control group and experimental group design. Two classees were selected through cluster random sampling from the eighth-grade student population. Class VIII A1 was assigned as the experimental group, receiving PBL with Magnetic Ball-based MBSW, while class VIII A2 served as the control group, using standard PBL without the magnetic ball aid. The findings show that the experimental grade that uses PBL assisted by Magnetic Ball MBSW has a more significant increase in learning outcomes than the control grade that uses the regular PBL model. The findings clearly show that PBL assisted with Magnetic Ball-based Student Worksheets is more effective than regular PBL in improving mathematics learning outcomes. While students’ initial abilities still play a role in overall achievement, the innovative use of MBSW offers a consistent advantage for all learners.